2008
DOI: 10.1111/j.1741-4369.2008.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Can the simple view deal with the complexities of reading?

Abstract: We review the Simple View of Reading (SVR) model and examine its nature, applicability and validity. We describe the SVR as an abstract framework for understanding the relationship between global linguistic comprehension and word-reading abilities in reading comprehension (RC). We argue that the SVR is neither a full theory of reading nor a blueprint for instruction. Nevertheless we argue that the model is helpful in conceptualising these broad skills and thus in planning for teaching and learning. We review e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
228
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(249 citation statements)
references
References 42 publications
12
228
0
9
Order By: Relevance
“…An influential theoretical account on reading, the Simple View of Reading (SVR; Gough & Tunmer, 1986), suggests that reading comprehension is the product of efficient decoding ability and linguistic comprehension. Since its conception, the SVR model has received considerable empirical support (for reviews, see Kirby & Savage, 2008;Stuart, Stainthorp, & Snowling, 2008) and has had a major influence on reading research and practice. There is, however, a need for longitudinal examinations of the SVR model in transparent orthographies (Florit & Cain, 2011).…”
mentioning
confidence: 99%
“…An influential theoretical account on reading, the Simple View of Reading (SVR; Gough & Tunmer, 1986), suggests that reading comprehension is the product of efficient decoding ability and linguistic comprehension. Since its conception, the SVR model has received considerable empirical support (for reviews, see Kirby & Savage, 2008;Stuart, Stainthorp, & Snowling, 2008) and has had a major influence on reading research and practice. There is, however, a need for longitudinal examinations of the SVR model in transparent orthographies (Florit & Cain, 2011).…”
mentioning
confidence: 99%
“…Nesse caso, refere-se à leitura em que a criança tem que aplicar as regras de correspondência entre letras e sons das palavras. Porém, a decodificação, no caso desse modelo, pode envolver um reconhecimento de palavras mais amplo, por uma rota lexical (leitura visual das palavras) ou pela aplicação de estratégias ortográficas (Kirby & Savage, 2008). Assim, o reconhecimento de palavras pode ser medido pela precisão ou acurácia na leitura de palavras ou pseudopalavras.…”
Section: O Simple View Of Reading E a Avaliação De Leituraunclassified
“…The empirical support for the Simple View in typically developing children is extensive (Catts, Herrera, Nielsen, & Bridges, 2015;Hulme & Snowling, 2014;Language and Reading Research Consortium, 2015;Ripoll Salceda et al, 2014), and the model has also been suggested to be useful as a theoretical framework for reading in deaf children (Chamberlain & Mayberry, 2000;Stone et al, 2015). At the same time, it has been suggested that more detailed specification of the cognitive mechanisms involved in the two components of the Simple View would promote greater understanding of reading development (Hulme & Snowling, 2014;Kirby & Savage, 2008;Stuart, Stainthorp, & Snowling, 2008), and attempts have been made to achieve this (e.g., Byrne et al, 2013;Kim & Phillips, 2014;Kim, 2015aKim, , 2015bTunmer & Chapman, 2012;Vellutino, Tunmer, Jaccard, & Chen, 2007).…”
Section: Learning To Comprehend Texts As a Sign Language Usermentioning
confidence: 99%